2018
DOI: 10.1029/2018gl077874
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Dissipation Around a Dipolarization Front

Abstract: Kinetic aspects of energy conversion and dissipation near a dipolarization front (DF) in the magnetotail are considered using fully kinetic 3‐D particle‐in‐cell simulations. The energy conversion is described in terms of the pressure dilatation, as well as the double contraction of deviatoric pressure tensor and traceless strain rate tensor, also known as the Pi‐D parameter in turbulence studies. It is shown that in contrast to the fluid dissipation measure, the Joule heating rate, which cannot distinguish bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 53 publications
2
51
2
Order By: Relevance
“…We used the same technique as Dunlop et al (2002) to calculate the spatial velocity gradients in Pi − D. Pi − D (i) and Pi − D (e) show small perturbation at the DF, while they exhibit large perturbation in the FPR, which were probably ascribed to the large ion and electron temperature anisotropies (Figures 1d and 1e). These features are different from those reported in Sitnov et al (2018), which demonstrates that both Pi − D (i) and Pi − D (e) reach positive peaks at DF.…”
Section: Figures 1j and 1kcontrasting
confidence: 99%
See 2 more Smart Citations
“…We used the same technique as Dunlop et al (2002) to calculate the spatial velocity gradients in Pi − D. Pi − D (i) and Pi − D (e) show small perturbation at the DF, while they exhibit large perturbation in the FPR, which were probably ascribed to the large ion and electron temperature anisotropies (Figures 1d and 1e). These features are different from those reported in Sitnov et al (2018), which demonstrates that both Pi − D (i) and Pi − D (e) reach positive peaks at DF.…”
Section: Figures 1j and 1kcontrasting
confidence: 99%
“…Our observations of 122 DFs probably sample these DFs at different Y locations, thus the average values shown in Figure are similar to the values averaged in Y in simulations (e.g., Lapenta et al, ). Recent three‐dimensional PIC simulations demonstrate that ripples developed on the DF cause the coexistence of the load (J · E > 0) and generator (J · E < 0) regions on the same DF (e.g., Lapenta et al, ; Pritchett, ; Sitnov et al, , ). The scale size of these ripples is on the order of the ion inertial length, which is significantly larger than MMS spacing (a few electron inertial length) in our events.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…This idea can be traced back to early works by Braginskii [63], which is generalized into the kinetic realm of collisionless systems by Del Sarto et al [64,65] as well. More recently, there is growing evidence that elucidates the role of pressure-strain interaction using numerical simulations [66] and observations [67].…”
Section: Introductionmentioning
confidence: 99%
“…Fu, Khotyaintsev, Vaivads, André, & Huang, ; Khotyaintsev et al, ; Schmid et al, ; Lu et al, ), earlier studies concluded that on subgyroscales, the DFs might be complex with embedded small scale dissipative layers (e.g. Angelopoulos et al, ; Balikhin et al, ; Sitnov et al, ) and that DFs cannot be described completely by the MHD theory and show a more diverse picture on small scales.…”
Section: Introductionmentioning
confidence: 99%